Impact of Distance Learning on Reading and Writing Ability in Elementary School Students - Andhini, Allyza Bunga; Sakti, Asri Wibawa (Universitas Pendidikan Indonesia (UPI), 2021)
Online learning is a new challenge for teachers and students, there must be many positive and negative impacts that occur, especially on the ability to read and write. This study aims to describe the impact of the implementation of online learning on the literacy skills of elementary school students based on previous studies and direct surveys of elementary school students to find out what impacts occur on students' literacy skills when learning is carried out online, both it's a positive or negative impact. This study uses a qualitative method with a descriptive design, while the research results are taken in the form of a one-group pre-test and post-test design. The results of this study showed an increase after being given material in the form of learning videos, but the role of the teacher during this online learning period was very important to continue to provide guidance and direct students so that their reading and writing skills remained good.